Study on the eye movement characteristics of the badminton practitioners of different levels regarding visual attention - Chen, Yanlan; Zulnaidi, Hutkemri; Syed Ali, Syed Kamaruzaman Bin (Frontiers in Psychology, 2023)
Badminton is a highly sophisticated, fierce, and competitive tactical game. It requires the same action of hitting a ball with different landing points. Therefore, the complexity of badminton practitioner's sports decision-making is relatively high. Accordingly, it is extremely important to study the difference between the eye movement characteristics of different levels of badminton athletes and the difference between the eye movement characteristics of different sports levels of amateur athletes. Overall, 15 students from the badminton professional training team of the Physical Education College of the Jiangxi Science and Technology Normal University and 15 students from the common public sports and badminton course were included as experimental participants in the present study. The laboratory experimental test on the virtual sports situation in badminton was conducted using an eye tracker. The eye movement index of both the badminton professionals and the experimental participants was recorded for statistical analysis, and the following results were obtained: (1) In the cognitive decision-masking task, the reaction time of the professional badminton practitioners was faster than that of the amateur practitioners. Similarly, in the intuitive decision-masking task, the reaction time and accuracy of the former were better than those of the latter. (2) The professional badminton practitioners' group was able to process and integrate the searched information in the process of sports attention selection information; although the amateur group was able to search and filter information, they were passive and could not actively process and assimilate the searched information. (3) The professional badminton practitioners could allocate their attention reasonably and process information in the process of attention transfer, while their amateur counterparts were affected easily by external interference factors. The level of motor intelligence of badminton practitioners in the professional group was higher than that of the amateur practitioners. Thus, these two groups of different levels showed attention transfer. (4) The mental skills of the professional group were higher than those of the amateur group.